An evaluation of a state-level fruit and vegetable incentive’s impacts on food and nutrition security among SNAP participants - Oddo, Vanessa M.; Leider, Julien; Tovar, Alison; Vadiveloo, Maya K.; Elenio, Emily; Powell, Lisa M. (Frontiers in Nutrition, 2025)
ObjectiveTo test the short-term effect of a state-level fruit and vegetable incentive (FVI) on food and nutrition security among Supplemental Nutrition Assistance Program (SNAP) participants.MethodsIn January 2024, Rhode Island (RI) implemented a FVI, which provided a $0.50 credit for every $1.00 spent on fresh FV up to $25/month. Using a difference-in-differences approach, we used separate adjusted logistic regression models to evaluate FVI impacts on household food and nutrition insecurity and perceived FV affordability, in RI relative to changes in the comparison site of Connecticut (CT), ~6 months after implementation.ResultsAt baseline, participants’ (N = 725) mean age was ~35 years old, ~95% were women, ~40% identified as Hispanic, and ~25% perceived that they could not afford FV. Food (55–59%) and nutrition (30–34%) insecurity were high in both states. After implementation, neither food [Odds Ratio (OR): 1.14; 95% Confidence Interval (CI): 0.84–1.55] nor nutrition insecurity (OR: 0.92; 95% CI: 0.63–1.34) changed in RI relative to CT. There were also no changes over time in perceived FV affordability in RI versus CT (OR: 0.80; 95% CI: 0.54–1.18).ConclusionWe did not observe short-term changes in food or nutrition insecurity associated with the FVI provided to SNAP participants. Future analyses should evaluate longer-term policy effects.